Professor Dr. Jorge Díaz Mayo: ethical and professional principles - Ena Paneque Ramos; Mireyi Meriño Martínez; Juan de Dios Hernández Beguiristaín (Universidad de Ciencias Médicas de La Habana, 2020)
This is to pay tribute to the recently deceased professor Dr. Jorge Díaz Mayo, who was admired and respected by everyone during all his work at "Enrique Cabrera" Hospital.  He was also an example of professional dedication not only to all the persons who worked directly with him but to those who, directly or indirectly, knew about his excellent qualities as a doctor and a human being.  He ended up his student´s formation with the Degree of Doctor of Medicine.  He distinguished himself for his prolific work in different medical centers for many years and he always kept the principles and ethics of upright and revolutionary doctor. He also distinguished himself for his collateral, political, and sports activities, as well as other actions for homeland defense.  He was considered an inspiring leader.